Mangostins and their bioactivities from garcinia Malaccensis HK.F - Bakhtiar, M. Taher; Darnis, Deny Susanti; Ahmad Zohri, Farah Syahidah; Arief Ichwan, Solachuddin Jauhari; Rezali, Mohd Fazlin (Penerbit USM, 2010)
Introduction: Guttiferae is a well-known family having a wide range of phytochemical constituents and bioactivities. Objectives: To investigate phytochemicals and bioactivities of Garcinia malaccensis. Materials and Methods: The isolated compounds were elucidated by spectroscopic methods. Antimicrobial activity was carried out by disc diffusion method. Antiproliferative activity was performed by tryphan blue exclusion and MTT assay. Antioxidant activity was conducted by DPPH radical scavenging. Results: Phytochemicals investigation of the stem bark of G. malaccensis lead to isolation of -mangostin, -mangostin and a triterpenoid. The main priority of this study’s activity was done on -mangostin as the compound was found as a major constituent. Results showed that -mangostin inhibits Staphylococcus aureus. The diameter of inhibition zone observed was 8 mm, minimum inhibition concentration (MIC) was 0.025 mg/mL and minimum bactericidal concentration (MBC) was 0.1 mg/mL. Dot-blot DPPH staining showed a positive antioxidant activity of -mangostin. In FTC method, -mangostin was proved to be a good lipid peroxidation inhibitor, whereas in DPPH free radical scavenging activity method, it has a very weak scavenging effects on free radicals. In the antiproliferative assay, -mangostin exhibited activity against K562 (IC50 20 μg/mL) and showed a weak activity against HSC3 and H1299 cell lines.